Estimation of IL-6 and IL-10 Levels in Patients with Iron Deficiency Anemia - Rabaa Khaled Abdel Salam; Saria Naji Mohsin (International Journal for Research in Applied Sciences and Biotechnology, 2021)
The study included a process of diagnosing and differentiating (60) cases of iron deficiency anemia patients (30) moderate iron deficiency anemia and (30) severe iron deficiency anemia, who are residents of the city of Kirkuk and its suburbs, and their ages ranged from 18-30 years of both sexes (30 males). And 30 females (with a control group of healthy (30) of whom (15 males and 15 females) and their ages ranged from 18-30 years. Anemia was diagnosed by following several basic measures such as the total blood picture count, which included the compacted cell volume (PCV), hemoglobin level, the RBCs red blood cell count, as well as the corpuscular hemoglobin rate (MCH) and the corpuscular volume rate (MCV) in addition to Other discriminatory measures such as serum iron and ferritin Serum Hepcidin, a marker of iron deficiency anemia, was significantly lower in the case of IDA patients. It has been found that IL-6 plays an important role in hepcidin regulation particularly in IDA. In the case of IDA, the level of IL-6 was significantly decreased. And we observed elevated IL-10 in IDA patients. We found that IL-10 has a role in hepcidin inhibition through IL-6. Inhibition.